Identification and Characterization of a Master Transcription Factor of Th1 Cells, T-bet, Within Flounder (Paralichthys olivaceus) - Tian, Hongfei; Xing, Jing; Tang, Xiaoqian; Chi, Heng; Sheng, Xiuzhen; Zhan, Wenbin (Frontiers in Immunology, 2021)
T-bet, a T-box family member, is a transcription factor essential for the differentiation of naive CD4+ T cells into Th1 cells that involved in both innate and adaptive immune responses. In this study, the transcription factor T-bet of flounder (Paralichthys olivaceus) was cloned and characterized, and its expression profile after infection was analyzed. T-bet+ cells were identified in flounder, and the expression and localization of T-bet in T lymphocyte subsets and B lymphocytes were investigated. Finally, the proliferation of T-bet+ cells, T lymphocyte subsets and B lymphocytes were studied after stimulation with IFN-γ, IL-2 and IL-6, respectively, and the variations of some transcription factors and cytokines in CD4+ T lymphocyte subsets were detected. The results showed that T-bet in flounder consists of 619 aa with a conserved T-box DNA binding domain. T-bet was abundantly expressed in the spleen, head kidney and heart, and it was significantly upregulated after infection with Vibrio anguillarum, Edwardsiella tarda and Hirame rhabdovirus, especially in the group of Edwardsiella tarda. A polyclonal antibody against recombinant protein of T-bet was prepared that specifically recognized the natural T-bet molecule in flounder. T-bet+ cells were found to be distributed in the lymphocytes of peripheral blood, spleen and head kidney, with the highest proportion in spleen, and the positive signals of T-bet were occurred in the cell nucleus. T-bet was also detected in the sorted CD4-1+, CD4-2+, CD8+ T lymphocytes and IgM+ B lymphocytes. In addition, T-bet+ cells, coordinated with CD4-1+ and CD4-2+ T lymphocytes, were proliferated after stimulation with IFN-γ, IL-2 and IL-6. Especially in sorted CD4-1+ and CD4-2+ T lymphocytes, IFN-γ and IL-2 were able to upregulate the expression of T-bet, and forming a positive feedback loop in Th1-type cytokines secretion. These results suggest that T-bet may act as a master transcription factor regulating flounder CD4+ T lymphocytes involved in a Th1-type immune response.